Late Complication of Knee Trauma: Isolated Common Peroneal Nerve Palsy - Erdil, Mehmet; Ceylan, Hasan Huseyin; Elmadag, Mehmet; ELMADAĞ, NUH MEHMET; Bilsel, Kerem; BİLSEL, İSMAIL KEREM; TUNCAY, İBRAHİM; TUNCAY, İBRAHİM (My University, 2014)
Introduction: Direct blunt or strain type traumas around the knee joint are not uncommon. In addition to osseous pathologies, soft tissue examination should be done meticulously. Otherwise additional problems may be neglected.